USE OF INFORMATION ENTROPIA METHOD IN THE DETERMINATION OF THE GENESIS OF THE MINERAL DEPOSITS (PANGEEA, 2025)
This paper presents a statistical method for determining the genesis of useful mineral deposits. It is based on the maximum degree of dispersion of some values on the definition domain of a statistical series, which can be represented graphically. By comparing graphical images of multiple fields or comparing with a standard graph, the genesis of some deposits can be determined quite accurately.
Keywords: information entropy; dispersion; genesis; mineral deposits